Dietary Bacillus coagulans supplementation improves liver health and modulates hepatic metabolic profiles in juvenile fourfinger threadfin (Eleutheronema tetradactylum) - Jing Li; Nuo Chen; An-Na Zheng; Shui-Ping He; Wei-Bin Liu; Jing-Heng Lu; Min-Xuan Jin; Lin-Juan Wang; Hui-Juan Zhang; Evodia Moses Mkulo; Bao-Gui Tang; Hui Zhou; et al. (Frontiers in Microbiology, 2026)
Introduction Dietary supplementation with probiotics has emerged as a promising strategy to enhance the health and productivity of farmed fish. However, the systemic metabolic effects of probiotics on the liver of marine aquaculture species, particularly the underlying molecular mechanisms, remain insufficiently explored. This study employed histopathological examination, biochemical assays, and non-targeted liver metabolomics to systematically evaluate the effects of dietary Bacillus coagulans on hepatic morphology, oxidative status, and metabolic profiles, and to elucidate the potential metabolic regulatory mechanisms underlying its protective action in fourfinger threadfin ( Eleutheronema tetradactylum ). Methods Juvenile E. tetradactylum were fed either a control diet or a diet supplemented with 1 × 10⁸ CFU/g B. coagulans . At the end of the eight-week feeding trial, liver samples were collected to evaluated the effects of dietary B. coagulans on the hepatic morphology, oxidative status, and metabolic profiles. Results B. coagulans supplementation improved hepatic tissue architecture, characterized by a more orderly cellular arrangement and reduced fibrosis. ALT activity was elevated in the B. coagulans group, indicating enhanced amino acid metabolism rather than hepatocellular injury. Activities of AKP, LZM, CAT, and SOD remained at healthy baseline levels with no significant intergroup differences, while MDA showed a non-significant downward trend. Metabolomics revealed 43 altered hepatic metabolites, with pathway enrichment indicating upregulated amino acid turnover, enhanced lipid metabolism (including cholesterol clearance), accelerated tricarboxylic acid cycle (increased isocitric acid), and elevated xanthine, a potent endogenous antioxidant. Conclusion Collectively, these findings demonstrated that B. coagulans supplementation safely optimizes hepatic metabolic flux and structural integrity, highlighting its potential as a highly effective functional additive to promote metabolic homeostasis in the aquaculture of E. tetradactylum .